The Language of Madness: Analyzing the Repetition and Obsession in The Short Story “The Tell-Tale Heart” through Discourse Analysis - Priscilla Abigail Giovanni Santoso; Ni Made Diana Erfiani Dewi; Yohanes Octavianus Lesu Awololon; Putu Chrisma Dewi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This study examines the discursive construction of madness in Edgar Allan Poe’s The Tell-Tale Heart through repetitive linguistic patterns that reflect psychological instability. By using a descriptive qualitative method within a Discourse Analysis framework, the data were analyzed through keyword frequency analysis, lexical repetition identification, and metafunctional interpretation of repeated keywords such as "louder," "eye," "heart," and "knew" based on Halliday's Systemic Functional Linguistics and Freud's psychoanalytic theory. The findings reveal that repetition has functions not only as a stylistic device, but also as a linguistic representation of paranoia, obsession, guilt, hallucination, and delusional certainty. From Halliday’s metafunctional perspective, in Textually, repetition contributes through lexical cohesion and thematic continuity, while in Ideationally, it reflects process shifts from objective reality into distorted mental experiences. From a psychoanalytic perspective, repetitive language patterns symbolize neurotic anxiety, Id dominance, Ego collapse, and defense mechanisms such as denial and projection. The conclusion of the study is that repetition in Poe's short stories goes beyond its cohesive function and serves as a discursive marker of psychological disintegration. These findings demonstrate the value of integrating stylistic, discourse-analytic, and psychoanalytic approaches in revealing the relationship between language patterns and psychological characterization in literary texts.